Antiplatelet agents in tissue factor–induced blood coagulation - Butenas, Saulius; Cawthern, Kevin M.; van't Veer, Cornelis; DiLorenzo, Maria E.; Lock, Jennifer B.; Mann, Kenneth G. (Blood, 2001)
Several platelet inhibitors were examined in a tissue factor (TF)–initiated model of whole blood coagulation. In vitro coagulation of human blood from normal donors was initiated by 25 pM TF while contact pathway coagulation was suppressed using corn trypsin inhibitor. Products of the reaction were analyzed by immunoassay. Preactivation of platelets with the thrombin receptor activation peptide did not influence significantly the clotting time or thrombin–antithrombin III complex (TAT) formation. Addition of prostaglandin E1 (5 μM) caused a significant delay in clotting (10.0 minutes) versus control (4.3 minutes). The prolonged clotting time is correlated with delays in platelet activation, formation of TAT, and fibrinopeptide A (FPA) release. In blood from subjects receiving acetylsalicylic acid (ASA or aspirin), none of the measured products of coagulation were significantly affected. Similarly, no significant effect was observed when 5 μM dipyridamole (Persantine) was added to the blood. Antagonists of the platelet integrin receptor glycoprotein (gp) IIb/IIIa had intermediate effects on the reaction. A 1- to 2-minute delay in clot time and FPA formation was observed with addition of the antibodies 7E3 and Reopro (abciximab) (10 μg/mL), accompanied by a 40% to 70% reduction in the maximal rate of TAT formation and delay in platelet activation. The cyclic heptapetide, Integrilin (eptifibatide), at 5 μM concentration slightly prolonged clot time and significantly attenuated the maximum rate of TAT formation. The disruption of the gpIIb/IIIa-ligand interaction not only affects platelet aggregation, but also decreases the rate of TF-initiated thrombin generation in whole blood, demonstrating a potent antithrombotic effect superimposed on the antiaggregation characteristics.